Training on Making Local Microorganisms (MOL) based on Mimosa Roots to Farmers Group in Jubung Village - Harsanti, Restiani Sih; Fariroh, Indri; Usmadi; Eriani Munandar, Denna; Sundahri; Stephani Pakpahan, Tioma; Aritonang, Firman (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Jubung Village is the largest soybean producer in Sukorambi District. Partners in this service are farmer groups in Jubung with the name of the Farmer Group